2016
DOI: 10.1002/jcph.691
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Transporter Polymorphisms on Drug Development: Is It Clinically Significant?

Abstract: Drug transporters are becoming increasingly recognized as relevant to the drug development process. This may be a reflection of increasing target complexity and the need for high-affinity interaction with drug targets that minimize off-target side effects. Moreover, as new molecular entities (NMEs) become larger in size and amphipathic in nature, interaction with drug transporters, both uptake as well as efflux, becomes increasingly likely. In some cases transporters may limit the absorption or organ-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 137 publications
(213 reference statements)
0
7
0
Order By: Relevance
“…The 1236C>T polymorphism is suggested to minimize ABCB1 functionality in vitro. 33) ABCB1 is highly expressed on the apical membrane of enterocytes in the entire intestine and on the bile canalicular membrane of hepatocytes, lower activity leads to higher absorption and lower elimination of erlotinib, thereby lowering CL/F. We previously reported that patients who were homozygous for the ABCB1*2 haplotype (1236TT-2677TT-3455TT) displayed higher plasma area under the curve (AUC) of erlotinib.…”
Section: Discussionmentioning
confidence: 99%
“…The 1236C>T polymorphism is suggested to minimize ABCB1 functionality in vitro. 33) ABCB1 is highly expressed on the apical membrane of enterocytes in the entire intestine and on the bile canalicular membrane of hepatocytes, lower activity leads to higher absorption and lower elimination of erlotinib, thereby lowering CL/F. We previously reported that patients who were homozygous for the ABCB1*2 haplotype (1236TT-2677TT-3455TT) displayed higher plasma area under the curve (AUC) of erlotinib.…”
Section: Discussionmentioning
confidence: 99%
“…25 McLean et al provide an assessment of potential impact of known polymorphisms in drug transporters and discuss if there is sufficient evidence to incorporate these polymorphisms in the drug development process. 26 Using rosuvastatin (a substrate of OATP transporters) as an example, Riedmaier et al discuss the utility of a physiologically based pharmacokinetic (PBPK) approach in conjunction with a power calculation algorithm to evaluate the required sample size to detect the effects of OATP1B1 polymorphisms. 27 Various disease states can alter the expression and activity of drug transporters.…”
Section: Role Of Transporters In Drug Developmentmentioning
confidence: 99%
“…Interestingly, Sugiyama and colleagues have shown that, in addition to differences in allelic frequencies of OATP transporters, intrinsic ethnic variability in the activity of OATP1B1 should also be considered to fully understand the ethnic variability in the plasma exposure of statins . McLean et al provide an assessment of potential impact of known polymorphisms in drug transporters and discuss if there is sufficient evidence to incorporate these polymorphisms in the drug development process . Using rosuvastatin (a substrate of OATP transporters) as an example, Riedmaier et al discuss the utility of a physiologically based pharmacokinetic (PBPK) approach in conjunction with a power calculation algorithm to evaluate the required sample size to detect the effects of OATP1B1 polymorphisms …”
mentioning
confidence: 99%
“…Inter‐individual variation in the human genome due to single‐nucleotide variations (SNVs), small‐scale insertions and deletions (InDels) and copy number variations (CNVs) may result in altered pharmacokinetic and pharmacodynamic characteristics of drugs leading to a lack of therapeutic efficacy or a risk for drug‐induced toxicity [15, 16]. Variations in genes encoding drug transporters have been documented to affect responsiveness to chemotherapeutic agents [15, 17]. Rarely, sensitivity of red cells to the direct toxicity of the drugs can lead to drug‐induced haemolytic anaemia [18–21].…”
Section: Introductionmentioning
confidence: 99%